STUDI ANALISIS TENTANG KEPADATAN PENDUDUK SEBAGAI SUMBER KERUSAKAN LINGKUNGAN HIDUP - Muannif Ridwan; Sri Hidayanti; Nilfatri Nilfatri (IndraTech, 2021)
The population density in an area will cause the space for an area to be narrower. Rapid population growth increases the demand for natural resources. Because humans are an integral part of the ecosystem, where humans live by exploiting their environment. Population issues and environmental damage are two things that are interrelated with one another. The occurrence of environmental damage can have an impact on human life at a macro level. Therefore, in the future we need wise efforts to maintain environmental sustainability and quality. This study uses a qualitative descriptive method with the type of research used is library research. The purpose of this research is so that readers can understand the population density as a source of environmental damage in a comprehensive manner. Conclusions of This study says that population density greatly affects several aspects related to life, including the availability of clean air, food, land and clean water and environmental pollution. We, as part of the population, must protect the surrounding environment or the environment in order to keep it clean so that we can breathe clean air without being polluted by garbage or pollution. Another way is to reduce the population growth rate by implementing government programs such as family planning (KB) and by not littering.Keywords: Population, Environment, Environmental Damage